Jewish veganism and vegetarianism studies and new directions - Labendz, Jacob Ari 1977-; Yanklowitz, Shmuly 1981- (Albany, New York SUNY, State University of New York Press, 2019)
"Jewish vegan and vegetarian movements have become increasingly prominent in recent decades, as more Jews adopt plant-based lifestyles. In this book, scholars, rabbis, and activists explore the history of veganism and vegetarianism among Jews and present compelling new directions in Jewish thought, ethics, and foodways. Jewish Veganism and Vegetarianism asks how Judaism, broadly considered, has inspired people to eschew animal products and how those choices have enriched and defined Jewishness. It offers opportunities to meditate on what makes Jewish veganism and vegetarianism particularly Jewish and to pursue the intellectual, religious, and historical roots of those movements. It also tests their boundaries, examines connections to other movements, and calls attention to divisions among Jewish vegans and vegetarians and to the resistance they have faced. In part one, "Studies," authors present Jewish veganism and vegetarianism in historical, literary, and sociological context: from the time of the Talmud until the present, in North America, Europe, and Israel, and among rabbis, chefs, artists, activists, punks, and farmers. Part two, "New Directions," is focused on contemporary currents in Jewish vegan and vegetarian thought. The authors represent the cultural, theological, and ideological diversity among Jews invested in such conversations and introduce prominent debates within their movements. As a whole, the volume presents a wide-ranging survey of the place of veganism and vegetarianism in Judaism past and present"--
Includes bibliographical references and index
Keywords: Vegetarianism -- Religious aspects -- Judaism; Veganism -- Moral and ethical aspects; Jewish ethics